2019
DOI: 10.3390/polym11020368
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sodium Trimetaphosphate on Chitosan-Methylcellulose Composite Films: Physicochemical Properties and Food Packaging Application

Abstract: Environmentally friendly food packaging currently attracts much interest. Sodium trimetaphosphate (STMP) finds specialized applications in food, but it is rarely used as a crosslinking agent. In this study, STMP was used as a crosslinking agent to prepare chitosan/methylcellulose composite films. Both antibacterial and physicochemical properties of the composite film were improved by crosslinking with STMP. The crosslinked films, with good antibacterial activity (~99%), had increased tensile strength, a higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 42 publications
(60 reference statements)
3
10
0
Order By: Relevance
“…These peaks are then shifted towards a higher WN when the concentration of glycerol is increased, which explains the interaction between glycerol and cations from the polymer–salt complex [ 62 ]. A comparable WN range for these bands was reported by Aziz et al [ 67 ] and Wang et al [ 68 ]. Another obvious sharp peak credited to the C–O stretching is observed at 1044, 1043, and 1039 cm −1 for CSMCD1, CSMCD2, and CSMCD3 electrolytes, respectively.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…These peaks are then shifted towards a higher WN when the concentration of glycerol is increased, which explains the interaction between glycerol and cations from the polymer–salt complex [ 62 ]. A comparable WN range for these bands was reported by Aziz et al [ 67 ] and Wang et al [ 68 ]. Another obvious sharp peak credited to the C–O stretching is observed at 1044, 1043, and 1039 cm −1 for CSMCD1, CSMCD2, and CSMCD3 electrolytes, respectively.…”
Section: Resultssupporting
confidence: 88%
“…Furthermore, the peaks related to the C=O and C=C stretchings can be observed at 1640 and 1441 cm −1 , respectively [ 67 , 68 , 69 ]. These peaks are then shifted towards a higher WN when the concentration of glycerol is increased, which explains the interaction between glycerol and cations from the polymer–salt complex [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…In line with the fi ndings of this research, it was reported that the color of the bioplastics from oxidized, crosslinked, and dual oxidation crosslinked lotus rhizome starch was clearer compared to the native material [Sukhija et al, 2019]. This is in agreement with the report by Wang et al [2019] who showed the colors and texture of fi lms made from chitosan methylcellulose crosslinking were more transparent and smoother due to the compactness of the starch molecules.…”
Section: Sensory Attributessupporting
confidence: 92%
“…Meanwhile, the Young's modulus of the PAAS bioplastics decreased with the concentrations of STMP/STPP up to 8% and afterwards remained constant at 12%. However, the elongation at break and Young's modulus of bioplastics from chitosan cross-linking methylcellulose using STMP 0.1 and 0.3% were found to be higher than these of the chitosan bioplastics [Wang et al, 2019].…”
Section: Mechanical Propertiesmentioning
confidence: 75%
“…Crosslinking contributes to decreases in the interaction of the polymer with water and to the structural integrity of the hydrogel, due to network formation. If blends of starch and CMC are processed, it is expected that CMC will also be susceptible to STMP action, as reported for another polysaccharides 19–21 . Thus, crosslinking should also take place between CMC chains, or between these and the starch chains.…”
Section: Introductionmentioning
confidence: 85%